GLP-1 receptor agonists as promising disease-modifying agents in WFS1 spectrum disorder - Panfili, Eleonora; Frontino, Giulio; Pallotta, Maria Teresa (Frontiers in Clinical Diabetes and Healthcare, 2023)
WFS1 spectrum disorder (WFS1-SD) is a rare monogenic neurodegenerative disorder whose cardinal symptoms are childhood-onset diabetes mellitus, optic atrophy, deafness, diabetes insipidus, and neurological signs ranging from mild to severe. The prognosis is poor as most patients die prematurely with severe neurological disabilities such as bulbar dysfunction and organic brain syndrome. Mutation of the WFS1 gene is recognized as the prime mover of the disease and responsible for a dysregulated ER stress signaling, which leads to neuron and pancreatic β cell death. There is no currently cure and no treatment that definitively arrests the progression of the disease. GLP-1 receptor agonists appear to be an efficient way to reduce elevated ER stress in vitro and in vivo, and increasing findings suggest they could be effective in delaying the progression of WFS1-SD. Here, we summarize the characteristics of GLP-1 receptor agonists and preclinical and clinical data obtained by testing them in WFS1-SD as a feasible strategy for managing this disease.